Peningkatan Kemampuan Literasi Digital Bagi Pelajar di Wilayah Kabupaten Maros Melalui Program Literasi Digital Sektor Pendidikan - Abdillah SAS; Ratnawati Gatta; Supriadi Syam; Ahmad Swandi; Muh Fadli Fauzi Sahlan; Nanang Hermawan (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2024)
This service aims to enhance the digital literacy skills of students in Maros Regency through an educational digital literacy program. The COVID-19 pandemic has prompted a shift in the learning paradigm from face-to-face to online, revealing the moderate to low levels of digital literacy among students. With a focus on digital ethics, a community engagement program was implemented in three schools, involving over 400 participants. The methodology included needs identification, activity planning, training execution, evaluation, and report compilation.Evaluation results demonstrate an improvement in the understanding and digital literacy skills of students, with a satisfactory percentage of success in post-test assessments. Collaboration among the government, university, and community was crucial to the success of this program. The impact encompasses a shift in the mindset of the younger generation regarding literacy education and the recognition of Maros Regency as a benchmark for digital literacy. The urgency of digital literacy is further emphasized through the Ministry of Communication and Information Technology of the Republic of Indonesia's program.